Migration policies and slum eradication in Ciudad de Buenos Aires during the last military dictatorship: the deportation of migrants from neighboring countries (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article deals with the subject of State violence in the eradication of shanty towns in the City of Buenos Aires, a plan executed by the last military dictatorship in Argentina (1976-1983). We will focus on deportation of migrants from neighboring countries, which was presented by the military government as a “voluntary return” of these inhabitants. To deconstruct this idea and show the different ways in which this violent process took place we resorted to the analysis of the written press of that period and to personal stories of interviewees that experienced this situation. We also included the analysis of documents by government and religious organizations. This allowed us to observe the construction of a collective memory on “massive deportations” and its revisions according to the context in which it is practiced. Finally, some thoughts are presented regarding the remembrance of eradications, deportations and institutional violence in the present and its links with urban policies implemented after the mili- tary dictatorship.
Keywords: Shanty towns; Buenos Aires; Memory; Military Dictatorship.